Korelasi Keterampilan Membaca Pemahaman Teks Laporan Hasil Observasi dan Keterampilan Menulis Teks Laporan Hasil Observasi Siswa Kelas X SMA Negeri 2 Bayang - Feronika, Niken Oktri; Gani, Erizal (Journal of Education Language and Innovation, 2024)
The research aimed to describe the level of reading comprehension skills, describe the level of writing skills, and analyze whether there was a correlation between reading comprehension skills and the skills in writing text reports from observations of class X students at SMA Negeri 2 Bayang. This type of research is quantitative research with descriptive methods. The research sample was taken at 15% using a simple random sampling technique. The instrument of this research is a test, namely an objective test of reading comprehension skills and a performance test of writing skills. There are three research results. First, the reading comprehension skills of the text of the observation report of class X students of SMA Negeri 2 Bayang are more than sufficient, with an average calculation of 67.07. Second, the skill of writing the text of the observation report of the students of class X of SMA Negeri 2 Bayang is at a sufficient qualification with an average calculation of 65.21. Third, a significant correlation exists between reading comprehension skills and observation report text writing skills with r_count>r_tabel, namely 0.976>0.297. H0 is rejected, and H1 is accepted because t_count (29.52) is greater than t_table (1.68). Thus, it can be concluded that reading comprehension skills are positively correlated with skills in writing observation report texts.